The Patterns and Appropriateness of Systemic Antifungal Prescriptions in a Regional Hospital in Hong Kong - Ryan Y. H. Leung; Jimmy Y. W. Lam (Antibiotics, 2025)
Introduction: The consumption of systemic antifungals is on the rise. However, a significant proportion of systemic antifungal prescriptions is inappropriate. Inappropriately prescribed antifungals are problematic, but there has been minimal emphasis on ensuring the appropriate prescription of systemic antifungals. Local studies regarding the patterns and appropriateness of antifungal prescriptions are also lacking. Materials and Methods: In this retrospective, single-centre, observational study, every in-patient prescription order of systemic antifungals in a regional hospital in Hong Kong between 1 May and 31 July 2023 was reviewed via electronic patient records. The appropriateness of a systemic antifungal prescription was assessed by its indication, dosage, duration and antifungal–concomitant drug interactions by a single reviewer. Results: A total of 177 prescriptions orders were collected. Itraconazole, micafungin and fluconazole were the most prescribed systemic antifungals. The haematology team, infectious disease team and ICU were the major systemic antifungal prescribers in this study. The overall appropriateness of systemic antifungal prescriptions was 27.7% (49/177), with an appropriateness of 72.9% (129/177) for indications, 57.1% (101/177) for dosage, 91.5% (162/177) for duration and 71.6% (127/177) for antifungal–concomitant drug interactions. Triazole antifungals had an overall prescription appropriateness of only 15% and were more likely to be prescribed inappropriately than non-triazole antifungals (p < 0.001). Common prescription pitfalls include (i) starting a systemic antifungal for sputum culture that grew Candida spp., (ii) debatable prophylaxis with itraconazole capsules, (iii) overlooking potentially serious antifungal–drug interactions. Conclusions: Inappropriate systemic antifungal prescription is not uncommon in Hong Kong. Establishing an antifungal stewardship programme in public hospitals may be beneficial.